Patient-derived xenograft model: Applications and challenges in liver cancer - Shuangshuang Dou; Yunfei Huo; Minghui Gao; Quanwei Li; Buxin Kou; Mengyin Chai; Xiaoni Liu; Yanjie Yin (Chinese Medical Journal)
Abstract. Liver cancer is one of the most common malignant tumors worldwide. Currently, the available treatment methods cannot fully control its recurrence and mortality rate. Establishing appropriate animal models for liver cancer is crucial for developing new treatment technologies and strategies. The patient-derived xenograft (PDX) model preserves the tumor’s microenvironment and heterogeneity, which makes it advantageous for biological research, drug evaluation, personalized medicine, and other purposes. This article reviews the development, preparation techniques, application fields, and challenges of PDX models in liver cancer, providing insights for the research and exploration of PDX models in diagnostic and therapeutic strategies of liver cancer.